Lathriobates manohardasi sp. nov. (Hemiptera: Gerromorpha: Gerridae) from Tamil Nadu, India, with a key to the species - Chandra, Kailash; Jehamalar, E. Eyarin (Zootaxa, 2012)
Lathriobates manohardasi sp. nov. is described and compared with known congeners. A key to the species of the genus of world is included.